2017
DOI: 10.1097/ccm.0000000000002699
|View full text |Cite
|
Sign up to set email alerts
|

Racial Disparities in Sepsis-Related In-Hospital Mortality: Using a Broad Case Capture Method and Multivariate Controls for Clinical and Hospital Variables, 2004–2013

Abstract: Our results indicate that hospital characteristics contribute to higher rates of sepsis mortality for blacks and Hispanics. These findings underscore the importance of ensuring that improved sepsis identification and management is implemented across all hospitals, especially those serving diverse populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 24 publications
1
39
1
Order By: Relevance
“…Between varieties of different hospital admission causes, the black race has historically been associated with lower resource utilization and higher in-hospital mortality [10][11][12][20][21][22]. However, among frail patients in our study, the white race was the strongest racial predictor of inpatient mortality.…”
Section: Discussioncontrasting
confidence: 49%
“…Between varieties of different hospital admission causes, the black race has historically been associated with lower resource utilization and higher in-hospital mortality [10][11][12][20][21][22]. However, among frail patients in our study, the white race was the strongest racial predictor of inpatient mortality.…”
Section: Discussioncontrasting
confidence: 49%
“…This approach has been suggested as the best way to operationalize these variables 29 and has been utilized by similar studies in the literature. 9,14,15 We considered the Asian race to include all people of East Asian, Southeast Asian, or South Asian descent, which is consistent with the United States Census Bureau definition. 30 Patients identifying as Native Hawaiians/Pacific Islanders, Native Americans/Alaskan Natives, as well as those with unspecified race or ethnicity, were categorized as Other.…”
Section: Covariate Data Collectionmentioning
confidence: 99%
“…Several studies have suggested that inter-hospital differences play a significant role in racial disparities of sepsis management. Minority patients are more likely to be treated at safety net hospitals and urban teaching hospitals, which often experience increased financial constraints while treating diverse patient populations [18,23,44,62,63]. Mayr and colleagues found that hospitals that treated higher proportions of black patients were less likely to receive antibiotics within 4 hours for pneumonia (odds ratio (OR) of 0.72 relative to whites) [63].…”
Section: Hospital-based Factorsmentioning
confidence: 99%